Rural cultural resourcefulness: How community music enterprises sustain cultural vitality - Gibson, Chris; Gordon, Andrea (Journal of rural studies, 2018)
This paper explores how musical performance and expression catalyse rural cultural resourcefulness amidst uncertainty and change. We describe and then challenge conceptions of rural vulnerability and resilience amidst substantial social, environmental and economic change. Rural populations are increasingly constituted as vulnerable subjects within state-expert modelling of economic and environmental resilience. Yet, cultural resources and capacities are seldom acknowledged. Community music provides an often invisible and overlooked example. In rural locations music may struggle to be a commercially viable industry, but takes different forms in diverse community music enterprises, including non-profit clubs, orchestras, ensembles, choirs and festivals. Such enterprises sustain engaged music participation despite challenges of isolation and lack of critical mass, and enable people to adjust to change and develop social networks. In so doing, community music contributes to an evolving, prosaic sense of rural cultural resourcefulness. We document how rural Australian musicians negotiate isolation, distance, and new circumstances, and foster alternative spaces for creativity. Geographic and socio-economic limitations triggered those with an insatiable desire to make and perform music to create their own opportunities through grassroots creativity. From this quotidian example we challenge state/expert conceptions of rural resilience. Resourceful creativities – focused on cultural vitality, process and everyday rewards rather than commercial successes – illustrate how rural people sustain cultural life amidst hardship, isolation and change. •State-expert conceptions of rural resilience neglect cultural resourcefulness.•Community music enterprises contribute to rural cultural resourcefulness.•Scant resources fuels creative frugality, and social relationships are deepened.•Isolation and sparse populations are challenges confronted, and a source of struggle.•Passions for music and values of endurance inform prosaic forms of cultural resilience.